Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1128/jvi.55.2.483-488.1985
|View full text |Cite
|
Sign up to set email alerts
|

Potent neutralizing activity associated with anti-glycoprotein D specificity among monoclonal antibodies selected for binding to herpes simplex virions

Abstract: Thirty-three monoclonal antibodies were selected for ability to bind to purified virions of herpes simplex virus and were shown by immunoprecipitation to react with one or another of the envelope glycoproteins. Only six of these antibodies exhibited potent neutralizing activity, and all six were specific for glycoprotein D. Two other anti-glycoprotein D antibodies and 25 antibodies specific for four other viral glycoproteins had much less potent, if any, neutralizing activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 37 publications
1
52
0
Order By: Relevance
“…Immunoprecipitation and SDS-PAGE Analysis. The antibodies used were as follows : ascitic fluid containing mAb to gC-1 (1173-1, 11474-1, 11475-1, 11512-3, 11529-1) or to gC-2 (III-188-4, III-211-1, III-596-1) were lyophilized and resuspended to original volume in PBS, pooling those antibodies specific for the same glycoprotein (14) . Ascitic fluid containing mAb MOPC-21, of unknown specificity, was treated as above and used as 'Abbreviation used in this paper: PBS/G/BSA, PBS with glucose and BSA.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitation and SDS-PAGE Analysis. The antibodies used were as follows : ascitic fluid containing mAb to gC-1 (1173-1, 11474-1, 11475-1, 11512-3, 11529-1) or to gC-2 (III-188-4, III-211-1, III-596-1) were lyophilized and resuspended to original volume in PBS, pooling those antibodies specific for the same glycoprotein (14) . Ascitic fluid containing mAb MOPC-21, of unknown specificity, was treated as above and used as 'Abbreviation used in this paper: PBS/G/BSA, PBS with glucose and BSA.…”
Section: Methodsmentioning
confidence: 99%
“…It is presumed that antibodies with a strong neutralizing activity, are directed against glycoproteins and antigenic sites important for viral infectivity, i.e., virus adsorption andlor penetration [Fuller and Spear, 1985;Highlander et al, 19871. In this context it was shown that monospecific and monoclonal antibodies 0 1989 ALAN R. LISS, INC. against gB, gD, and gH exhibited neutralizing activity without complement [Spear 1984;Para et al, 1985;Fuller and Spear, 1985;Gompels and Minson, 1986;Highlander et al, 1987 I, whereas antibodies against gC, gE, and gG did not [Norrild, 1980;Para et al, 1982;Sullivan and Smith, 19871. Furthermore, gC and gE appear to be nonessential proteins for infectivity of HSV [Holland et al, 1983;Longnecker and Roizman, 1986;Neidhardt et al, 19871.…”
Section: Introductionmentioning
confidence: 96%
“…The loglo 50% neutralizing titers ranged from <1.0 to almost all isolates reacted with the higher titers than those of the HSV-2 standard strain 186. The lower neutralizing titers against the strain used as immunogen than against other virus strains were previously reported by other investigators (18). For each MAb, the mean and standard deviation of the neutralizing titers between that of the HSV-2 isolates and the HSV-2 standard strain 186 were statistically tested for a homogeneity of variance using Barlett's chi-squared test.…”
Section: Characterization Of Isolates By 50% Neutralization End Pointsmentioning
confidence: 86%
“…At least 8 glycoproteins of HSV have been identified; they are designated as glycoprotein B (gB), gC, gD, gE, gF, gG, gH, and gI (5, 10,17,23). Among these, gD is a major target for virus-neutralizing antibodies (8,18) .…”
mentioning
confidence: 99%